MANAJEMEN SEKOLAH RAMAH ANAK PAUD INKLUSI - Alisa Alfina; Rosyida Nurul Anwar (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This study aims to understand the management of Child-Friendly Schools (SRA) of PAUD inclusive which was carried out at PAUD Cendekia Kids School and the All Kids Learning House in Madiun City, East Java. This research uses a qualitative approach with case study. The technique of collecting data is done through interviews, observation, and documentation. While the data analysis technique starts from the data display, data reduction, until drawing conclusions. The results showed that; First, PAUD Scholar Kids School and the All Kids Learning House have their respective characteristics in implementing inclusive PAUD management, by adjusting to the conditions of existing institutions. secondly, child-friendly inclusive PAUD management at Cendekia Kids School is in the process of finding shapes while the All Kids Learning House had a shape; third, the obstacles in trying to realize the SRA at Cendekia Kids School are different from those at the All Kids Learning House; fourth, the biggest obstacle to management is human resource management competence; fifth, the two institutions do not have legality as child-friendly PAUD, but in its implementation, it is already appropriate as a child-friendly inclusive PAUD.